Examining the Effect of Social Media Advertising Features on Customer Perceived Value and Brand Love in the Retail Industry - Jalal Rajeh Hanaysha; Khaled M.K. Alhyasat (Telematics and Informatics Reports)
This article examines the effect of social media advertising features (interactivity, entertainment, informativeness, and perceived relevance) on customer perceived value and brand love within the retail industry. The required main data for this research was gathered from customers of large hypermarkets in the United Arab Emirates (UAE) via an online survey. Throughout the data collection process, a convenience sampling technique was used. In total, 307 valid questionnaires were analyzed via the PLS-SEM approach. The analysis depicted that perceived value has a positive impact on brand love. The findings also indicated that entertainment, perceived relevance, informativeness, and interactivity positively affect perceived value. Finally, the outcomes also exhibited that all the social media advertising features significantly and positively impact brand love. This paper brings a key contribution to the existing body marketing literature by clarifying the impact of social media advertising elements on perceived value and brand love in the retail setting.